MODEL INVESTASI DANA INFAK BAITUL MAL ACEH: KONSEP BISNIS PEMBANGUNAN PABRIK PADI - Mahdi, Sayed; Ahmadsyah, Israk; Jais, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The mandate of the Governor of Aceh Regulation No. 8 of 2022 regarding the management of Zakat and Infak emphasizes the management roles of Zakat and Infak along with the distribution mechanism and investment model according to Sharia principles. Baitul Mal Aceh, as the institution managing ZISWAF, must develop important strategic programs to reduce poverty in Aceh province, increase income redistribution, and enhance the welfare of the Acehnese people. The agricultural sector is essential to this study's consideration as an investment model for BMA Infak funds because it is the primary livelihood of the Acehnese people. This study uses a qualitative approach by applying SWOT analysis and the Business Model Canvas. The findings support the notion that combining BMA waqf assets with a partnership structure with the PEMA and the concepts of profit sharing, and ijarah will improve the investment model of BMA infaq funds with the mechanism of building a rice mill.